Prevalence and pattern of amblyopia among children attending at tertiary eye care centre in Eastern India - Mondal, Mobina; Ghosh, Asim Kumar; Dutta, Subrata (International Journal of Research in Medical Sciences, 2022)
Background: The objective of this study was to determine the prevalence and pattern of amblyopia of children attending at tertiary eye care centre in eastern India. Methods: A cross-sectional study was conducted from April 2020 to May2021 among children (5-15 years age) at regional institute of ophthalmology, medical college, Kolkata, underwent visual acuity assessment, detailed ocular examinations and cycloplegic refractions. Results: A total of 500 children are taken in the study, out of which 264 (52.8%) were males. The age range was 5-15 years with 479 (95.8%) within the ages of 5 to 10 years. Amblyopia was detected in 57 (11.4%). Refractive amblyopia (58.4%) was the most common type of amblyopia out of which anisometropic amblyopia accounted for 74.6%. Unilateral amblyopia was observed in 80.5%. All the types of amblyopia were more common within the age group of 5-10 years. Conclusions: More common children are affected with amblyopia within the ages of 5 to 10 years with refractive amblyopia.